Effect on groundwater quality from proximal surface water bodies and effect on arsenic distribution in Bangladesh: geochemical controls - Barua, Shovon (Kansas State University, 2015)
The province (upazila) of Matlab in SE Bangladesh is highly affected with elevated concentrations of dissolved As content and widespread fecal contamination in untreated drinking waters. The study area is sedimentologically composed of thick floodplain deposits of Holocene age overlying Plio-Pleistocene grey fine to coarse sands with considerable clays (consisting of Dupi Tila formation). The goal of the current study is to understand the possible impact of co-occurrence of dissolved organic carbon (along with As release) and fecal indicator bacteria (e.g., E.coli) in aquifers from shallow to deep groundwater quality in this area. Nineteen groundwater (spanning a depth range of 14 to 240 m) samples and nine surface water samples (eight ponds and one canal in proximity to the piezometer nests) were collected from four different piezometric nests within north and south Matlab Upazila in Bangladesh during the monsoonal season (Jun-Jul 2014). The analyses of dissolved organic carbon (DOC) and its fluorescence properties indicate that the chemical character of DOC from shallow to intermediate groundwaters (<150 m) and surface water is dominated by more aromatic and humic materials than deeper groundwaters. Both groundwaters and surface waters may receive humic substances leached from soil and/or from the cellular constituents and exudates of indigenous aquatic organisms. Dissolved organic carbons in groundwater and surface waters are composed of predominantly UVA and UVC-humic like along with tryptophan like components. Only 15% of total C is modern carbon at shallowest depths (<30 m) in groundwaters. The recharge source of groundwaters is from local precipitation, with or without some evaporation before infiltration as depicted by the δ2H and δ¹⁸O variations and the water is infiltrating through mostly terrestrially derived weathered sediments into the aquifers. The type of water in the study area is Ca-Na-HCO₃⁻ type. More toxic and soluble As (III) is present in shallow groundwaters (<30 m). High concentrations of As (V) and As[subscript (t)] are observed high in shallow and intermediate depth wells (<150 m). The most probable number based on the Colilert test and qPCR result for E.coli suggest that unprotected surface waters are harbingers for high microbial population compared to hand pumped wells. However, the very low observed concentrations of cultured E. coli (<1-10 MPN/100 mL) and E. coli DNA (<40 Copies/100 mL) in the wells indicates that the abundance of E.coli cells decrease rapidly with residence time in oligotrophic aquifers. Thus, it may be suggested that more humic DOC in shallow and intermediate groundwaters may be involved in complexation or other biogeochemical reactions that may mobilize As in groundwater. The non-indigenous bacteria can be the primary producers of DOC in the aquifers which can be utilizing surface derived DOC.
Keywords: Arsenic; Characterization of dissolved organic carbon; Groundwater quality; Ground-surface water interaction; Geochemical controls; Fecal indicator bacteria (E. coli); Geology (0372)